2017
DOI: 10.1128/aac.02140-16
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Genotypic Cutoff Values To Measure Antimicrobial Resistance in Salmonella

Abstract: Whole-genome sequencing (WGS) has transformed our understanding of antimicrobial resistance, helping us to better identify and track the genetic mechanisms underlying phenotypic resistance. Previous studies have demonstrated high correlations between phenotypic resistance and the presence of known resistance determinants. However, there has never been a large-scale assessment of how well resistance genotypes correspond to specific MICs. We performed antimicrobial susceptibility testing and WGS of 1,738 nontyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…As expected, we observed that 718 out of 725 S. enterica isolates (99.0%) with one or more bla CMY - family genes were resistant to amoxicillin-clavulanic acid. As observed previously (51), other beta-lactamases conferred decreased or intermediate susceptibility to amoxicillin-clavulanic acid (Fig. 3).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As expected, we observed that 718 out of 725 S. enterica isolates (99.0%) with one or more bla CMY - family genes were resistant to amoxicillin-clavulanic acid. As observed previously (51), other beta-lactamases conferred decreased or intermediate susceptibility to amoxicillin-clavulanic acid (Fig. 3).…”
Section: Resultssupporting
confidence: 87%
“…S. enterica displayed high consistency for both ciprofloxacin and nalidixic acid (Table 2). When decreased susceptibility (R or I) is used as the breakpoint for ciprofloxacin (51), S. enterica isolates had high positive predictive values (PPV = 0.891) and high negative predictive values (NPV = 0.997). For nalidixic acid, the positive predictive value was quite low (PPV = 0.3).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, from the analysis by the Resfam databases it became apparent that Bacillus VU-DES13 contains 13 additional b-lactams when compared to the BCT-7112 T genome, which may explain its high resistance to the b-lactam penicillin. This would support the genotypic cutoff concept, linking the distribution of resistance alleles to MIC (Tyson et al, 2017). Antibiotic producers can evolve mechanisms to protect themselves from the compounds they are producing (Hopwood, 2007).…”
Section: Discussionmentioning
confidence: 67%
“…A total of 470 E. coli antibiograms were submitted directly by COMPARE partners while 107 were imported from the US CDC database (n = 31) or previous publications (n = 76) 10,11 .…”
Section: Current Contentmentioning
confidence: 99%
“…Contributing institutions for AST data: Amsterdam UMC 1 , APHA 11 , DTU 2 , FM 7 , OUCRU 13 , SSH 12 , UNIBO 10 .…”
Section: Acknowledgementsmentioning
confidence: 99%